2017
DOI: 10.1016/j.jval.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Complete Revascularization for Patients with Multivessel Disease Undergoing Primary Percutaneous Coronary Intervention

Abstract: Objectives: To determine the cost-effectiveness of complete revascularization at index admission compared with infarct-related artery (IRA) treatment only, in patients with multivessel disease undergoing primary percutaneous coronary intervention (P-PCI) for ST-segment elevation myocardial infarction. Methods: An economic evaluation of a multicenter randomized trial was conducted, comparing complete revascularization at index admission to IRA-only P-PCI in patients with multivessel disease (12-month follow-up)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…Effectively treating patients to reduce recurrent events could reduce time spent in the hospital, and it is for such reasons that recurrent events have been included in some recent cost-effectiveness studies. 18,19 Limitations This analysis has limitations. Analyses of recurrent events may overestimate the contribution of patients experiencing MACE early in a trial, 8 cannot differentiate between cardioprotective mechanisms of a drug that may differ between first and subsequent events 16 and do not account for the decreasing compliance that is nominally reported as CV outcomes trials progress.…”
Section: Discussionmentioning
confidence: 99%
“…Effectively treating patients to reduce recurrent events could reduce time spent in the hospital, and it is for such reasons that recurrent events have been included in some recent cost-effectiveness studies. 18,19 Limitations This analysis has limitations. Analyses of recurrent events may overestimate the contribution of patients experiencing MACE early in a trial, 8 cannot differentiate between cardioprotective mechanisms of a drug that may differ between first and subsequent events 16 and do not account for the decreasing compliance that is nominally reported as CV outcomes trials progress.…”
Section: Discussionmentioning
confidence: 99%
“…In this trial, 3L was administered at baseline and then 2 months and 11 months post-randomization. 8) CvLPRIT: The CvLPRIT (Complete-compared to Lesion-Only Revascularisation for Myocardial Infarction) trial 30,31 randomized patients presenting with ST-segment elevation myocardial infarction with bystander stenosis to an infarctonly strategy (only treat the blocked artery that caused the heart attack) versus complete revascularization (treat the blocked artery and also treat any narrowed arteries that may cause heart attacks in future). In this trial, 3L was administered immediately before discharge and at 12 months postdischarge.…”
Section: ) Cardera: the Combination Of Anti-rheumatic Drugs In Earlymentioning
confidence: 99%
“…-Five studies that identified themselves as RCT and eight other studies that identified themselves as clinical trials [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: : Total Number Of Articles After Applying Inclusion/exclusimentioning
confidence: 99%